Diversity, distribution and significance of truffles in Türkiye - Akyüz, Mehmet; Kirbağ, Sevda (CRC Press, 2025)
The fungi kingdom is the second largest biological community after insects (Purvis and Hector, 2000). They evolved about 1.8 billion years ago, making them an ancient, diverse and heterogeneous group of organisms (Hawksworth, 1991; Kirk et al., 2008). Fungi play a crucial role in ecosystems as endophytes, pathogens and saprobes. They exhibit considerable variation in morphology, ranging from unicellular to filamentous to sporocarps, and possess diverse life cycles. Many fungi form specialized associations with other organisms, especially plants. Fungi displays an enormous diversity of taxa, with their broad ecologies, different life cycle strategies, and morphologies ranging from single-celled water chytrids to molds, yeasts, dermatophytes, and macrofungi (Hawksworth and Lucking, 2017). © 2025 Kandikere R. Sridhar and Sunil K. Deshmukh. All rights reserved.